Postgraduate Student’s Attitudes towards Investment Decision-making: A Comparative Study between India and Nigeria - Pandey, Dr. Laxmi; Karamchandani, Devanshu; Dixit, Anjali; Obinwa, Etoo Emmanuel (Journal of International Conference Proceedings, 2023)
This comparative study aims to explore and analyze the attitudes of postgraduate students towards investment decision-making in the contexts of India and Nigeria.Through a survey conducted among 181 postgraduate students in both the countries, this research investigates their perceptions, preferences, and approaches when making investment decisions. By employing a structured questionnaire, the study assesses factors influencing investment choices, risk tolerance, information sources, and overall financial literacy levels. Drawing on the psychological, social and economic distinctions between India and Nigeria, the research seeks to identify similarities and differences in investment attitudes among the two populations. The findings not only contribute to the literature on factors affecting investment behavior but also provide insights for financial educators, policymakers, and financial institutions to tailor strategies that enhance the investment decision-making skills of postgraduate students in both nations. Finally, this study shows the importance of educational background in shaping individual investment preferences and choices.